BIOM-25. DETERMINATION OF LEVELS OF SMALL MOLECULAR WEIGHT THIOLS AND DISULFIDES IN MOUSE AND HUMAN NORMAL BRAIN AND GLIOBLASTOMA TISSUE. (14th November 2022) - Shaik, Kamal; Margaryan, Tigran; Sanai, Nader; Tovmasyan, Artak
Abstract: BACKGROUND: Small molecular weight (SMW) thiols play an essential role in many biochemical processes, particularly in maintaining redox homeostasis. Herein, we report on the development and qualification of a sensitive and rapid LC-MS/MS method for the determination of oxidative stress biomarkers glutathione (GSH), cysteine (Cys), glutathione disulfide (GSSG), cystine (CySS), as well as the interrelated precursors and products methionine (Met), homocysteine (Hcy), cystathionine (Cysth), gamma glutamyl-cysteine (Glu-Cys), and cysteinylglycine (Cys-Gly) in both mouse and human normal brain and glioblastoma tissue. METHODS: Mouse and human tissue samples were homogenized with N -ethylmaleimide solution to prevent thiol oxidation. Analytes were then extracted from homogenate samples by protein precipitation with 2% formic acid in acetonitrile. Separate calibration curves were prepared for thiols and disulfides in analytical solutions using stable isotope-labeled internal standards (IS). Three levels of quality control samples were prepared in mouse and human brain homogenates. The detection was performed on Sciex QTRAP 6500 + mass spectrometer in positive electrospray ionization mode. RESULTS: The concentration ranges of 0.04-40 µmol/L for Glu-Cys/Hcy, 4-400 µmol/L for Met/GSH/Cys/Cys-Gly and 0.05-20 µmol/L for GSSG/CySS/Cysth were established using a linear regression model. A gradient elution was applied on Intrada Amino Acid column to achieve the optimal chromatographic separation with a 5 minute total run time. At least three precision and accuracy runs were conducted on different days. The stability of analytes in biological matrix and in analytical solutions has been tested at room temperature, 4 °C, and -80 °C for appropriate sample preparation, analysis, and storage. CONCLUSIONS: A bioanalytical method to quantify a panel of SMW thiols and disulfides has been successfully developed, qualified, and utilized to assess the levels of these biomolecules in mouse normal brain and glioblastoma tissue as well as in glioblastoma tissue of patients enrolled in the sonodynamic therapy clinical trial (NCT04559685).